THE RELATIONSHIP BETWEEN THE APPLICATION OF SASAK'S LOCAL WISDOM-BASED LEARNING AND STUDENTS' CRITICAL THINKING SKILLS - Fadli, Adi (Universitas Islam Negeri Mataram, 2023)
This research examines the correlation between the utilization of Sasak's indigenous knowledge in the learning process and the development of critical thinking abilities among students of Islamic education in the region of West Nusa Tenggara. The present study employed a quantitative research approach, utilizing a survey design methodology to gather data. The primary instrument employed for data collection was a critical thinking abilities questionnaire. The data underwent analysis by the application of a regression test, employing a significance threshold of .05. The findings indicate that there exists a statistically significant correlation between the implementation of learning based on Sasak's local wisdom and the development of critical thinking abilities among Islamic education students in West Nusa Tenggara. Furthermore, the study demonstrates that the utilization of Sasak's local wisdom-based learning contributes to a 30% improvement in critical thinking skills. Therefore, it is imperative for higher institutions to promote the integration of local wisdom-based learning approaches in order to effectively attain the learning objectives associated with 21st-century capabilities.